2013
DOI: 10.5194/acpd-13-27053-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The importance of vertical velocity variability for estimates of the indirect aerosol effects

Abstract: The activation of aerosols to form cloud droplets is dependent upon vertical velocities whose local variability is not typically resolved at the GCM grid scale. Consequently, it is necessary to represent the sub-grid-scale variability of vertical velocity in the calculation of cloud droplet number concentration.

This study uses the UK Chemistry and Aerosols community model (UKCA) within the Hadley Centre Global Environmental Model (HadGEM3), coupled for the first time to an explicit aerosol activation…
Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
(93 reference statements)
1
8
0
Order By: Relevance
“…These observations were comparable with those of κ-parameter estimated from H-TDMA measurements (κ ~0.07-0.08) in the Amazonia (Rissler et al, 2004(Rissler et al, , 2006, as well as consistent with previous studies on water uptake of carbon-dominated aerosols (e.g., Petters et al, 2009;Carrico et al, 2010;Dusek et al, 2011;Engelhart et al, 2012). Although κ-values derived from ground-based observations of biomass-burning aerosols are generally less than 0.1, with sufficient atmospheric updraft velocity (i.e., strong adiabatic cooling) the aerosols can serve as CCN and influence cloud microphysical and radiative properties (e.g., West et al, 2014). Reutter et al (2009) have further investigated the sensitivity of the formation of cloud droplets to κ-values under pyro-convective conditions and found that a 50% change in κ alters the droplet concentration by more than 10% for aerosols with very low hygroscopicity (κ < 0.05) in the updraft-limited regime.…”
Section: Hygroscopicity and Aerosol-cloud-radiation Interactionsupporting
confidence: 69%
“…These observations were comparable with those of κ-parameter estimated from H-TDMA measurements (κ ~0.07-0.08) in the Amazonia (Rissler et al, 2004(Rissler et al, , 2006, as well as consistent with previous studies on water uptake of carbon-dominated aerosols (e.g., Petters et al, 2009;Carrico et al, 2010;Dusek et al, 2011;Engelhart et al, 2012). Although κ-values derived from ground-based observations of biomass-burning aerosols are generally less than 0.1, with sufficient atmospheric updraft velocity (i.e., strong adiabatic cooling) the aerosols can serve as CCN and influence cloud microphysical and radiative properties (e.g., West et al, 2014). Reutter et al (2009) have further investigated the sensitivity of the formation of cloud droplets to κ-values under pyro-convective conditions and found that a 50% change in κ alters the droplet concentration by more than 10% for aerosols with very low hygroscopicity (κ < 0.05) in the updraft-limited regime.…”
Section: Hygroscopicity and Aerosol-cloud-radiation Interactionsupporting
confidence: 69%
“…K.CA use the same droplet nucleation scheme, SPRINTARS and ECHAM6-HAM apply a lower bound on N d (16,17) that clearly substantially limits the droplet number sensitivity to CCN for clean conditions such as the preindustrial (18). Differences in updraft velocity and in natural emissions could also contribute to the diversity (19), but additional experiments without lower bounds would be required to determine the contribution of the lower bound to the diversity.…”
Section: Structural Uncertainty For Each Termmentioning
confidence: 99%
“…The tropospheric chemistry part of UKCA is described in O'Connor et al (2014). HadGEM3 uses a prognostic treatment of rain formulation (Abel and Boutle, 2012) and employs a prognostic cloud fraction and condensation cloud scheme (PC2) (Wilson et al, 2008), in which the cloud droplet number concentration is diagnosed from the expected number of aerosols that are available to activate at each timestep (West et al, 2014). Cumulus convection is represented by a mass flux convection scheme based on Gregory and Rowntree (1990) with various extensions (Walters et al, 2014).…”
Section: Discussionmentioning
confidence: 99%